The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jpcc.8b00875
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Unassisted Overall Photocatalytic Seawater Splitting on GaN-Based Nanowire Arrays

Abstract: Large-scale, clean, efficient, and sustainable hydrogen production from water is one of the major goals in solar-to-fuel conversion as the sun and water represent the two most abundant and geographically balanced free resources available on earth. Considering that most of the liquid water available on the earth’s surface is present in the form of seawater, H2 generation from seawater splitting is highly desirable for large-scale practical and economical application. Herein, we report on the first demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 25 publications
1
73
0
Order By: Relevance
“…Therefore, these 3 samples had similar behaviors, without plateau photocurrents, that show they are eligible for use PEC in seawater. Previous works reported that the generation of oxygen can occur by 2 major reactions: the OER from water oxidation and photodissociation of hypochlorite (HClO), which was produced from the reaction between water and chlorine (Cl 2 ) dissolved in seawater . For instance, it was verified that a small fraction of Cl − remained in solution and it was suggested that the chlorine oxidation reaction may be an intermediate process for seawater splitting .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, these 3 samples had similar behaviors, without plateau photocurrents, that show they are eligible for use PEC in seawater. Previous works reported that the generation of oxygen can occur by 2 major reactions: the OER from water oxidation and photodissociation of hypochlorite (HClO), which was produced from the reaction between water and chlorine (Cl 2 ) dissolved in seawater . For instance, it was verified that a small fraction of Cl − remained in solution and it was suggested that the chlorine oxidation reaction may be an intermediate process for seawater splitting .…”
Section: Resultsmentioning
confidence: 99%
“…Previous works reported that the generation of oxygen can occur by 2 major reactions: the OER from water oxidation and photodissociation of hypochlorite (HClO), which was produced from the reaction between water and chlorine (Cl 2 ) dissolved in seawater. [34,35] For instance, it was verified that a small fraction of Cl À remained in solution and it was suggested that the chlorine oxidation reaction may be an intermediate process for seawater splitting. [34] These reports used an artificial solution and a filtrated natural seawater where the pH was 6.5, the same used in this work.…”
Section: Photoelectrochemistry and Eismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover,operando ambient pressure X-ray photoelectron spectroscopy (APXPS) has also show groundbreaking ability for instanceb ys patially-resolvingt he surfacechemical states of aworkingsolid state electrochemical cell (SOC), providing critical understanding for the rational design of such devices. [75] Finally,t he combinationo fn ovel and smart energy materials design studied at atomics cale and in "real" operating conditions by operando X-ray spectroscopies at synchrotron radiation facilities worldwide is an ideal situation for the current and future generation of scientists to unravel new phenomena as well as establishing quantitative correlations between structural properties, electronic structure and physical/chemical properties of materials [76][77][78] to not only improveour fundamental knowledge but also going beyond as imple incremental increase of device efficiency by breakthrough fundamental and appliedd iscoveries in materials science, condensed matter physics,c hemistry and biology.S uch advances in energy materials, characterizations techniques as wella sb etter fundamental and applied understanding should allow scientists and engineers of all origins to efficiently contribute( and potentially solve) current societal and environmental crucial issues that is, novel carbon-zero sustainable energy resources such as stable and efficient hydrogen generation from (sea)water splitting [79,80] for ac leanerand safer world.…”
Section: Discussionmentioning
confidence: 99%